Development of a handwriting recognation system based on Malaysians' handwritten characters - 214963 Gan, Huay Loo; Marzuki Khalid, supervisor; Fakulti Kejuruteraan Elektrik (2005)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2005